Concomitant anti-platelet therapy in warfarin-treated patients undergoing cardiac rhythm device implantation: A secondary analysis of the BRUISE CONTROL trial. (1st August 2019) - Essebag, Vidal; AlTurki, Ahmed; Proietti, Riccardo; Healey, Jeff S.; Wells, George A.; Verma, Atul; Krahn, Andrew D.; Simpson, Christopher S.; Ayala-Paredes, Felix; Coutu, Benoit; Leather, Richard; Ahmad, Kamran; et al.
Abstract: Background: Anti-platelet therapy is commonly used in patients receiving oral anticoagulation and may increase bleeding risk among patients undergoing cardiac implantable electronic device (CIED) surgery. We sought to determine the proportion of anticoagulated patients who are concomitantly receiving anti-platelet therapy, the associated risk of clinically significant hematoma (CSH), and the proportion of patients in whom anti-platelet usage is guideline-indicated. Methods: A secondary analysis of the Bridge or Continue Coumadin for Device Surgery Randomized Controlled Trial (BRUISE CONTROL). Patients who were receiving warfarin, had an annual predicted risk of thromboembolism of ≥5% and were scheduled to undergo non-emergent CIED surgery were randomized to continued warfarin versus heparin bridging. In the current analysis, patients were divided into those receiving anti-platelet therapy and those not receiving anti-platelet therapy. The incidence of CSH was compared in both groups. The proportion of patients on potentially inappropriate and potentially interruptible antiplatelet therapy was estimated. Results: All 681 patients enrolled in BRUISE CONTROL were included, of whom 280 received and 401 did not receive anti-platelet therapy. Anti-platelet therapy increased the risk of CSH (relative risk, 1.72; 95% confidence interval (CI), 1.09 to 2.72; P = 0.02). Of the 280 patients receiving anti-platelet therapy, 97 (34.6%) had no guideline indication for concomitant anti-platelet therapy and an additional 146 (52.1%) were on anti-platelet therapy that could potentially have been interrupted around CIED surgery. Conclusions: Concomitant anti-platelet therapy in patients receiving anticoagulation is associated with a significant risk of CSH. The majority of concomitant anti-platelet therapy is potentially inappropriate or interruptible. Trial registration: clinicaltrials.gov Identifier: (NCT00800137 ) Highlights: Patients may be receiving inappropriate concomitant anti-platelet therapy. Concomitant anti-platelet therapy is associated with significant bleeding. Appropriate concomitant anti-platelet therapy is potentially interruptible.